Aplikasi Asap Cair Tempurung Kelapa Rendah Benzo[a] Pyrene untuk Meningkatkan Kualitas Se’i Sapi Bali - Liberius Krisantus Dheko; Dodi Darmakusuma; Pieter Rihi Kale (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2017)
This research has been conducted in the District Amarasi Kupang district to obtain liquid smoke coconut shell, Bogor Agricultural Institute Laboratory tested compounds benzo[a]pirene.dan total bacteria in meat, an integrated research laboratory distillation liquid smoke Undana perform and get the value of organoleptic and agricultural polytechnic Laboratory Kupang test the chemical quality beef cattle se'i Bali. The research was conducted over 2 months ie April 26 until June 26, 2016. This study aims to determine the content benzo[a]pirene. lowest in liquid smoke coconut shell by doing some distillation processes to be applied to the meat of cattle se'i Bali. The material used is coconut shell as much as 20 kg, 5 kg of fresh beef taken on the part of the muscle. The basic design is used, a completely randomized design (CRD) with 6 treatments and 3 repetitions so obtained 18 experimental units. Data was analyzed using non-parametric analysis of Kruskal Wallis test and analysis methods Analysis of Variance (ANOVA). If there are differences among the treatments then continued by Least Significant Difference (LSD). The results showed: Total Bacteria contained in meat P≤0,05 se'i not significantly different from the treatment of liquid smoke to the meat using traditional se'i P0. 6,6x106 P1. 6,2x106 P2. 5,4x106 P3. 1,7x106 P4. 4,46x103 P5. 3,0x103 while the chemical quality beef cattle se'i P≤0,01 Bali very significant effect of each treatment. conclusion on the research is: the more the percentage of liquid smoke, the number of bacteria in the cow se'i diminishing and the average chemical quality beef cattle se'i Bali will increase.